Poly (dimethyl siloxane) films in porous media - Ayalur-Karunakaran, Santhosh; Stapf, Siegfried (Diffusion Fundamentals, 2009)
Poly (Dimethyl siloxane) thin films were prepared by solvent evaporation method in porous alumina hosts. The thickness of these layers ranged from multilayer to sub-monolayer. Different NMR methods (FFC relaxometry, transverse relaxation, 1H Double quantum NMR) were applied to study the dynamics and order in these thin films. We found that dynamic restrictions and order increased with decreasing layer size. The increase of a short component of T2 from CPMG curves was attributed to the thawing of the adsorbed chains as seen in the decrease of the short component from Hahn echoes.